Implementasi Kebijakan Desa dalam Melestarikan Budaya Lokal Melalui Tradisi Pengajian Rutin di Desa Parmompang, Kecamatan Panyabungan Timur - Muhammad Sholih; Santika Dewi; Salma Harahap; Syamsiah Depalina Siregar (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This article discusses the implementation of village policies to preserve local culture through religious study activities held every Friday morning and evening in Parmompang Village, East Panyabungan District. The religious study conducted by the Nauli Namora Boru (NNB) group in collaboration with the local community is not only a religious activity but also part of a long-standing tradition. Using qualitative descriptive methods, data was obtained through observation, interviews, and documentation. The results of the study indicate that the village policy in supporting these religious study activities is being implemented well. This is evident in the enthusiasm of the community, the active role of local organizations, and the consistent implementation. The impact is not only maintaining the continuity of the religious study tradition but also strengthening religious values, togetherness, and social harmony in the Parmompang Village community. The main findings indicate that the implementation of village policies in supporting pengajian activities has brought significant impacts. First, these activities are able to preserve the continuity of pengajian as part of the local cultural identity. Second, they serve as an effective form of non-formal education in instilling religious, moral, and ethical values in the younger generation. Third, pengajian activities strengthen social bonds through the spirit of togetherness, mutual cooperation, and the creation of social harmony within the community. Therefore, the village policy in Parmompang Village can be considered successful, as it not only sustains the continuity of religious culture but also contributes to the realization of a religious, harmonious, and character-driven society.